An adaptive identification method based on the modulating functions technique and exact state observers for modeling and simulation of a nonlinear MISO glass melting process - Byrski, Witold; Drapała, Michał; Byrski, Jędrzej (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents new concepts of the identification method based on modulating functions and exact state observers with its application for identification of a real continuous-time industrial process. The method enables transformation of a system of differential equations into an algebraic one with the same parameters. Then, these parameters can be estimated using the least-squares approach.
Keywords: continuous systems; modulating functions; system identification; exact state observer; glass forehearths